Effect of Apnea-Induced Hypoxia on Cardiovascular Adaptation and Circulating Biomarkers of Oxidative Stress in Elite Breath-Hold Divers - Solich-Talanda, Magdalena; Żebrowska, Aleksandra; Mikołajczyk, Rafał; Kostorz-Nosal, Sabina; Ziora, Dariusz; Jastrzębski, Dariusz; Siermontowski, Piotr (Frontiers in Physiology, 2021)
Given the previous evidence that breath-hold diving is a cause of physiological stress, this study aimed to determine whether a combination static and dynamic apnea would affect total oxidant status, nitric oxide, heat shock proteins and cardiovascular parameters in elite freedivers. Thirteen finalists of the World and European championships in swimming pool breath-hold diving participated in the study. Whole-body plethysmography and electrocardiography was performed to determine the cardiorespiratory variables at baseline and during the simulation static apnea. An assessment of the heart rate, blood oxygen saturation and biochemical variables was performed before and in response to a combination of a static followed by a dynamic apnea. Static and dynamic breath-holding had a significant effect on oxidative stress, as evidenced by an increase in the total oxidant status/capacity (TOS/TOC) (p<0.001). The post apnea concentrations of heat shock proteins 27 (HSP27) were significantly elevated (p<0.03, but total antioxidant status (TAS), HSP90, HSP70 and nitric oxide (NO) changes were not significant. levels under the influence of the static and dynamic breath-hold protocol. A significant positive correlation between HSPs and TAS (r = 0.63; p < 0.05) as well as NO levels was associated with beneficial cardiovascular adaptation. An increase in serum HSP27 levels mediated in nitric oxide levels could explain its important role in improving cardiovascular functions in elite freedivers. Further studies are necessary to explain the exact mechanisms of breath holds training of cardiovascular adaptation responsible for maintaining adequate oxygen supply in elite divers.